Minimizing skills and training gaps through professional development course - James A Ejiwale (Journal of Education and Learning (EduLearn), 2019)
Many companies that are striving to expand their development and production are finding it difficult to do so successfully. This is due to the shortage of qualified employees to help sustain their competitive edge in the global market. This dilemma is due to skills gaps; more importantly a mismatch between available jobs and skills. It is imperative to prepare the workforce for technical jobs and as well to find a lasting solution to eradicate the effect of skills and training gaps on college graduates. This paper addresses the causes of skills and training gaps and the need to minimize the impact of skills and training gaps through professional development.